The Effect of Serif and San Serif Typeface of Luxury Fashion Logotype on Chinese Consumers’ Brand Perception - Wang, Zheng; Musdi, Shanat; Louis Ringah, Kanyan (Sciedu Press, 2022)
An appropriate and well-designed logotype is essential to create brand awareness and positive brand perception. The effect of different typefaces has not been well researched in the luxury fashion sector. This paper expands on previous findings on typeface applications, in which two studies test the impact of Serif and San Serif typefaces, and three experiments test the effects of San and Serif typefaces on brand perception. Study 1 (N = 102) tests the visual complexity of Serif and San Serif typefaces; study 2 (N = 134) further investigates the visual simplicity and perceived luxury; and study 3 (N = 92) studies the brand gender of the two typefaces. The results of these three studies suggest that Serif typeface is more complex in structure than San Serif typeface. However, it does not have too much impact on the perceived luxury. Male consumers have greater gender cognitive differences than female consumers, and the San Serif typefaces are considered to be more masculine than Serif typefaces.